2017
DOI: 10.1021/acs.inorgchem.6b01952
|View full text |Cite
|
Sign up to set email alerts
|

Diazoalkanes in Low-Coordinate Iron Chemistry: Bimetallic Diazoalkyl and Alkylidene Complexes of Iron(II)

Abstract: Addition of trimethylsilyldiazomethane and its conjugate base to β-diketiminate-iron precursors gives novel dinuclear complexes in which the bridges are either diazomethane derivatives or an alkylidene. One product is an unusual bridging alkylidene complex containing two three-coordinate iron(II) centers. On the other hand, syntheses using the deprotonated diazomethane give two bridging diazomethyl species with binding modes that have not been observed in iron complexes previously. In the presence of coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…Bottom,l eft:reversible Fe 2 + /Fe 3 + oxidation wave at À0.98 V. Bottom,right:i rreversible reduction wave at À3.09 V. paramagnetic product has ap oorly resolved 1 HNMR, but intriguingly hasapeak in the IR spectrum at 2038 cm À1 ,s uggesting that the N 2 moiety is still present ( Figure S35). [45,46] Single crystal X-ray confirmed that the N 2 from the diazoalkane had not been lost, and we had synthesized the diazoalkane complex, [( (S,S)À1, 2ÀCy,BMe 2 TC H )Fe(N 2 CPh 2 )] (8) ( Figure 4). Diazoalkane binding to transition metals is quite complex, [47] and few diazoalkane complexes have been prepared on iron.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Bottom,l eft:reversible Fe 2 + /Fe 3 + oxidation wave at À0.98 V. Bottom,right:i rreversible reduction wave at À3.09 V. paramagnetic product has ap oorly resolved 1 HNMR, but intriguingly hasapeak in the IR spectrum at 2038 cm À1 ,s uggesting that the N 2 moiety is still present ( Figure S35). [45,46] Single crystal X-ray confirmed that the N 2 from the diazoalkane had not been lost, and we had synthesized the diazoalkane complex, [( (S,S)À1, 2ÀCy,BMe 2 TC H )Fe(N 2 CPh 2 )] (8) ( Figure 4). Diazoalkane binding to transition metals is quite complex, [47] and few diazoalkane complexes have been prepared on iron.…”
Section: Resultsmentioning
confidence: 89%
“…Addition of diazodiphenylmethane to 6 caused a color change to dark brown with no apparent N 2 evolution. This paramagnetic product has a poorly resolved 1 H NMR, but intriguingly has a peak in the IR spectrum at 2038 cm −1 , suggesting that the N 2 moiety is still present (Figure S35) . Single crystal X‐ray confirmed that the N 2 from the diazoalkane had not been lost, and we had synthesized the diazoalkane complex, [( ( S , S )−1, 2−Cy,BMe 2 TC H )Fe(N 2 CPh 2 )] ( 8 ) (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…1113 Recently, Holland and co-workers have reported on the synthesis of the singly alkylidene bridged high-spin Fe II dimer of type D by using diazoalkanes as a μ 2 -C 2– ligand source, formally having been a four electron donor ligand. 14…”
Section: Introductionmentioning
confidence: 99%
“…[16] Tentatively, this complex forms through a 1,3-trimethylsilylium shift, resulting in [Co II -CN-NSiMe 3 ], which-upon loss of [NTMS]-provides the Co II -CN complex. [17] Complex 1 was treated with NBu 4 F in thawing THF (Scheme 3). Monitoring the reaction by 19 F NMR spectroscopy confirmed the release of Me 3 SiF.…”
mentioning
confidence: 99%